Comparing lidar analysis and field documentation in archaeological surveys: feature recognition, quantification, and land-use modeling with the Small Cycladic Islands Project - Knodell, Alex R.; Levine, Evan I.; Wege, Samuel; Fielder-Jellsey, Michaela; Athanasoulis, Demetrios (Journal of Greek Archaeology, 2025)
Over six field seasons (2019–2024), the Small Cycladic Islands Project (SCIP) has conducted systematic pedestrian surveys of 87 uninhabited islands across the Cycladic archipelago. In 2022 and 2023, SCIP acquired lidar data over 97 currently uninhabited islands in the Cyclades, working with the Thessaloniki-based company Aerophoto. The goals of this work were several: (1) to supplement and expand our knowledge of areas already surveyed by SCIP (2019–2021), many of which are heavily obscured by vegetation cover; (2) as a precursor and guide to our own pedestrian survey work in 2022–2024, especially in large islands that could not be surveyed at the same level of intensity as smaller ones; (3) to supplement investigations of other islands that are well known and have been surveyed by other projects using other methods (Delos, Rheneia, and Despotiko); and (4) to cover areas where it is not possible for the project to carry out pedestrian survey work, due to issues of accessibility, size, or other constraints (Gyaros and Antimilos).